Measuring the importance of using modern accounting systems in meeting the administrative work in the hospitality sector - Al - Adsani, Nasser Ahmed (Journal of Economic, Administrative and Legal Sciences, 2018)
This study is used to measure the importance of the role of modern accounting information systems, to meet the administrative requirements necessary and to make appropriate decisions in the planning and control process, with the strategies and objectives of the establishment, compare them with the traditional methods of profitability and organization. To achieve the objective of the study, the researcher used the analytical descriptive method to answer the study questions in an ideal manner. Based on this, the researcher leaned a questionnaire and distributed it to 285 employees in the local establishments of the hospitality sector in Kuwait, and 21 employees were interviewed in the local establishments of the hospitality sector in Kuwait. After the analysis of the data collected through questionnaires and interviews through different means of analysis, the researcher reached a number of results, the most important of which is that the use of modern accounting software and accounting systems in the hospitality sector is of great interest and it is expected that the volume of uses and transactions in this field will increase in Kuwait In the next few years, so the study recommended that enterprises in the hospitality sector should focus on investing in the technological and human infrastructure properly.
Keywords: modern accounting systems; hospitality sector; administrative work